Validation and quantification of major biomarkers in 'Mahasudarshan Churna'- an ayurvedic polyherbal formulation through high-performance thin-layer chromatography - Prabhjot Kaur; R. C. Gupta; Abhijit Dey; Tabarak Malik; Devendra Kumar Pandey (BMC, 2020)
Abstract Background Mahasudarshan Churna (MC) is a polyherbal Ayurvedic medicine that is employed in fever (especially chronic type), cold and malaria, improvement of digestion and appetite, removes toxins from the blood, boosts immunity and protects against common bacterial infections. Methods Validation and quantification of oleanolic acid (OA), ursolic acid (UA), mangiferin (M), gallic acid (GA), quercetin (Q) and curcumin (C) in commercial MC formulations by HPTLC method. Mobile phase, hexane: ethyl acetate: acetone (16.4: 3.6: 0.2, v/v) was used for the separation of OA and UA; ethyl acetate: glacial acetic acid: formic acid: water (20: 2.2: 2.2: 5.2 v/v) for the development of M; and toluene: ethyl acetate: formic acid (13.5: 9: 0.6 v/v) for the separation of GA, Q and C in crude sample extracts. Visualization and scanning were performed at λ = 530 nm for OA and UA, at λ = 254 nm for M and at λ = 366 nm for GA, Q and C. In addition, HPLC-PDA analysis was used to confirm the HPTLC results. Results Major bio-active compounds in MC formulations were oleanolic acid (1.54-1.78%), mangiferin (1.38-1.52%) and gallic acid (1.01-1.15%); followed by ursolic acid (0.79-0.98%), curcumin (0.45-0.67%) and quercetin (0.22-0.34%). Conclusion Analysis of bio-active compounds in the present study was performed using HPTLC methods and later HPTLC results were compared with HPLC. These two methods give comparable results and there was no statistically significant difference between the mean values for all extracts. Present study concluded that this HPTLC technique is low cost, fast, precise, and accurate which can be employed for the quantification of xanthonoid (M), triterpenoids (OA, UA) and phenolics (GA, Q and C) in samples/formulations. Furthermore, present HPTLC method can be conveniently employed for routine quality control analysis of all the six marker compounds in marketed Ayurvedic/herbal formulations.